Work organisation and economic evaluation of vine graft production - Ferencz, Árpád (Acta Agraria Kaposváriensis, 1998)
Those involved in vine graft production now produce on the basis of advance orders; this can be attributed principally to the beneficial conditions of state support in Hungary. The lack of financial resources constitutes a drawback with respect to serious investment in, for example, cold storage and mother plantation. Therefore it is considered justified to examine profitability to determine the requirement for investment from external sources and to facilitate development in this direction. Further economic evaluations are necessary for the accomplishment of this task.
Keywords: vine graft production; economic evaluation; requirement for state assistance